Pengaruh Personal Branding Agen, Kualitas Produk, dan Citra Merek terhadap Keputusan Pembelian Skincare Canbeauty pada Agen Canbeautyofficial Gresik - Deavita Lusi Rahmawati; Ni Made Ida Pratiwi; Awin Mulyati (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
This study aims to analyze the effect of agent personal branding, product quality, and brand image on purchasing decisions for Canbeauty skincare at Canbeauty Official Gresik agents. This research is motivated by the increasing competition in the skincare industry and increasing consumer awareness of product safety and quality. The research method used is quantitative with a descriptive approach and multiple linear regression analysis. The sample of this study consisted of consumers who had consulted and purchased Canbeauty skincare products at Canbeauty Official Gresik agents. The results showed that the three independent variables Personal Branding, Product Quality, and Brand Image simultaneously influence Purchasing Decisions. Partially, each variable also has an influence on purchasing decisions. The implications of this research can be a marketing strategy for companies and agents to increase consumer loyalty and trust through strong Personal Branding, maintained Product Quality, and positive Brand Image.